Moral Anxiety In Charles Dickens's Hard Times: A Psychoanalytic Approach - Sholikhati, Emila (2004)
The major problem of this study is how the major character escapes from the anxiety, resulted from unhanded problems she encounters. The aim of this study is to identify the relation between the causes of anxiety and the ways to escape from structural and psychoanalytic analysis. In so doing, the study focuses on the major character, namely Louisa. The benefit of the study is to give some contributions in the application of psychological approach in literary study and to fulfill the requirement for getting bachelor degree in English Department. The study uses library data, the primary data is taken from the novel it self, while the secondary data is taken from some criticism and information needed. The method of data collection is descriptive and hermeneutics. The study employs sigmoid Freud's psychoanalysis to answer the problem. The outcome of the study shows that there is a close relationship between a work of literature and psychological phenomena. The psychological analyses, specifically psychoanalytic conclude that anxiety occurs as a result of a strained relation among the elements of personality system, namely id, ego and superego. Based on Sigmund Freud's theory, the anxiety experienced by Lou isa as the major character in this novel is categorized into moral anxiety